A strategy to improve enzymatic saccharification of wheat straw by adding water-soluble lignin prepared from alkali pretreatment spent liquor. (August 2018) - Jiang, Bo; Yu, Jiyao; Luo, Xufeng; Zhu, Yangsu; Jin, Yongcan
Graphical abstract: Highlights: Water-soluble lignin (WSL) has positive effect on substrate enzymatic hydrolysis. Sulfonated alkaline lignin was more efficient than water-soluble alkaline lignin. Effect of WSL on enzymatic hydrolysis depends on the existence of substrate lignin. Cellulase-WSL interaction may reduce the non-productive adsorption of cellulase. A strategy for improving substrate enzymatic hydrolysis by WSL addition is proposed. Abstract: In this work, the effect of water-soluble lignin on the enzymatic saccharification of alkali-pretreated wheat straw was investigated using soluble fraction (WAL) and sulfomethylated insoluble fraction (SAL) of alkaline lignin from the pretreatment spent liquor as additives. Results showed the total sugar recovery was improved for pretreated solids but was inhibited for bleached substrate with adding a certain amount of WAL or SAL. The interaction between adsorption domain of cellulase and water-soluble lignin was considered to be the potential reason for reducing the non-productive adsorption of residual lignin to cellulase. SAL was more efficient on enhancing the enzymatic saccharification than WAL, and the effect of WAL and SAL on glucan recovery was rather different from that of xylan recovery. Based on the obtained results, a strategy to improve the enzymatic saccharification of lignocellulosic biomass by adding water-soluble lignin prepared from alkali pretreatment spent liquor was proposed.